2019
DOI: 10.1007/s42452-019-0437-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalysis, photoluminescence, and anti-bacterial activities of nanosize Ag: green synthesized via Rauvolfia tetraphylla (devil pepper)

Abstract: In the current study, we have built up a novel, green approach technique for the synthesis of silver nanoparticles (Ag NPs) from Rauvolfia tetraphylla leaves extract. The synthesized nanoparticles were thoroughly characterized using different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, UV-Vis spectroscopy (UV-Vis), scanning electron microscopy, energy-dispersive X-ray spectroscopy and transmission electron microscope analysis. It is confirmed as a cubic phase with ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…[70][71][72][73] The rate of degradation was found to be increased with the increase of irradiation time of UV light, whereas the absorbance peak of MB dye was decreased with the increase in time in the presence of Ag 2 O photocatalyst. As can be seen from Figure 10, the absorbance of MB has intensely decreased, resulting in 85.18% of degradation in 4 h. [74]…”
Section: Photocatalytic Degradationmentioning
confidence: 87%
“…[70][71][72][73] The rate of degradation was found to be increased with the increase of irradiation time of UV light, whereas the absorbance peak of MB dye was decreased with the increase in time in the presence of Ag 2 O photocatalyst. As can be seen from Figure 10, the absorbance of MB has intensely decreased, resulting in 85.18% of degradation in 4 h. [74]…”
Section: Photocatalytic Degradationmentioning
confidence: 87%
“…It shows that the formation of OH · increases with an increase of time. This OH · is responsible for the degradation of organic dyes [46].…”
Section: Detection Of Oh · Radicalsmentioning
confidence: 99%
“…The catalytic activity of metal nanoparticles has extensively investigated in the field of water pollution remediation. Many research groups have demonstrated the effective utilization of noble metal NPs or metal NP incorporated composites systems as a suitable redox catalyst for the degradation of various organic pollutants like dyes, drugs and aromatic nitro compounds [12][13][14][15][16][17][18][19]. Additionally unique electrochemical features and high conductivity of AgNPs identifies AgNPs as a good candidate for selective and sensitive monitoring of biomolecules and pharmaceuticals [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the biosynthesis of metal nanoparticles (MNPs) have been proposed as a cost-effective and eco-friendly substitute to chemical methods. Many studies have been demonstrated the biosynthesis of AgNPs mediated by the microorganism or by phytochemicals or enzymatic synthesis [11,18,19,[29][30][31][32][33]. Among the biological methods, photosynthesis which involves reduction by phytochemicals derived from plants seems to be the superior choice.…”
Section: Introductionmentioning
confidence: 99%